Vývoj a porovnání regulace bankovního sektoru v USA a EU - Kostygova, Ekaterina (2024)
The bachelor thesis deals with banking regulation in the USA and the EU, mainly regarding the implementation of the Basel III Accord. The main emphasis is to examine the current regulatory frameworks in the USA and the EU and distinguish the differences between them. At the outset, general information regarding the purpose and nature of banking regulation is provided. The second and third parts examine the development and current regulatory requirements in the USA and the EU, focusing on capital and liquidity requirements. The last compares and evaluates two regulatory frameworks and the approaches to the calculation of requirements. The thesis concludes that the regulatory framework in the USA is insufficient as it concentrates more on regulating large banks and does not properly protect small and medium-sized banks. In contrast, the regulatory framework in the EU is more balanced with requirements that are less dependent on the bank’s size. As a result, banks in the EU are more liquid and capitalised.